Assessment of corneal nerve regeneration after axotomy in a compartmentalized microfluidic chip model with automated 3D high resolution live-imaging - Bonneau, Noémie; Potey, Anaïs; Blond, Frédéric; Guerin, Camille; Baudouin, Christophe; Peyrin, Jean-Michel; Brignole-Baudouin, Françoise; Réaux-Le Goazigo, Annabelle (Frontiers in Cellular Neuroscience, 2024)
Damage to the corneal nerves can result in discomfort and chronic pain, profoundly impacting the quality of life of patients. Development of novel in vitro method is crucial to better understand corneal nerve regeneration and to find new treatments for the patients.Existing in vitro models often overlook the physiology of primary sensory neurons, for which the soma is separated from the nerve endings. To overcome this limitation, our novel model combines a compartmentalized microfluidic culture of trigeminal ganglion neurons from adult mice with live imaging and automated 3D image analysis offering robust way to assess axonal regrowth after axotomy.Physical axotomy performed by a two-second aspiration led to a reproducible 70% axonal loss and altered the phenotype of the neurons, increasing the number of substance P-positive neurons 72 h postaxotomy. To validate our new model, we investigated axonal regeneration after exposure to pharmacological compounds. We selected various targets known to enhance or inhibit axonal regrowth and analyzed their basal expression in trigeminal ganglion cells by scRNAseq. NGF/GDNF, insulin, and Dooku-1 (Piezo1 antagonist) enhanced regrowth by 81%, 74% and 157%, respectively, while Yoda-1 (Piezo1 agonist) had no effect. Furthermore, SARM1-IN-2 (Sarm1 inhibitor) inhibited axonal regrowth, leading to only 6% regrowth after 72 h of exposure (versus 34% regrowth without any compound)Combining compartmentalized trigeminal neuronal culture with advanced imaging and analysis allowed a thorough evaluation of the extent of the axotomy and subsequent axonal regrowth. This innovative approach holds great promise for advancing our understanding of corneal nerve injuries and regeneration and ultimately improving the quality of life for patients suffering from sensory abnormalities, and related conditions.